ECONOMIC IMPLICATIONS OF THE SOFTWARE INDUSTRY DEVELOPMENT IN SERBIA - Rastovac, Dragan; Dukić, Dragan; Ničić, Milica (Ekonomija - teorija i praksa, 2022)
Based on current data and documents available from relevant statistical organizations, this paper presents and analyzes statistical and economic indicators of software product development in Serbia, with a parallel review of adequate data for the European Union. A descriptive method for comparative analysis was used for the analysis of data related to the number of enterprises, number of employees, average realized earnings per employee, and the realized turnover in Telecommunications, Computer programming, and Information sectors. Due to considerable differences in terms of areas that countries cover and the strength of their economies, trends in the mentioned areas and monitored and analyzed parameters (e.g. employment, average earnings and total exports, i.e. turnover of services) were observed. The obtained results indicate that Serbia has exceptional potential in the field of computer programming, while other activities in the field of information dissemination and communication, for now, do not record significant growth. On the other hand, in the European Union, the analyzed areas show stability of the analyzed parameters in the observed period. This indicates that a high level of development has been reached in the EU and that significant progress is now being made more slowly. With this development trend, the field of computer programming will probably be the first economic area in which Serbia can catch up with the European level.